IMD World Competitiveness Rankings - Karen Hogan; Niall Judge; Linda Kane (National Competitiveness and Productivity Council (NCPC), 2022)
Ireland is ranked 11th out of 63 economies in the IMD's World Competitiveness Yearbook 2022, gaining two places from 2021. Amongst the euro area countries, Ireland is ranked the 3rd most competitive, an improvement of one place since last year. Ireland improved its ranking in two of the four major competitiveness pillars: Economic Performance and Government Efficiency, and while the Business Efficiency pillar remained unchanged, Ireland's ranking in the Infrastructure pillar deteriorated in 2022.
Keywords: 330